2017
DOI: 10.1002/2017gl075703
|View full text |Cite
|
Sign up to set email alerts
|

A Low Viscosity Lunar Magma Ocean Forms a Stratified Anorthitic Flotation Crust With Mafic Poor and Rich Units

Abstract: Much of the lunar crust is monomineralic, comprising >98% plagioclase. The prevailing model argues the crust accumulated as plagioclase floated to the surface of a solidifying lunar magma ocean (LMO). Whether >98% pure anorthosites can form in a flotation scenario is debated. An important determinant of the efficiency of plagioclase fractionation is the viscosity of the LMO liquid, which was unconstrained. Here we present results from new experiments conducted on a late LMO‐relevant ferrobasaltic melt. The liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…The corrected Uhlmann et al (1974) viscosity η = 0.54 Pa-s is higher than the one derived from our data η = 0.33 Pa-s; however the difference is not unacceptable considering experimental uncertainties. Recently, Sehlke and Whittington (2016) measured the 1 atm viscosity of a synthetic high-Ti lunar basalt (LM sample, 9.52 wt% TiO 2 ), and obtained η = 0.19 Pa-s at 1850 K, which extrapolates to η = 0.14 Pa-s at 1906 K. This value is again close to our present estimate for black glass composition η = 0.15 Pa-s at 1 atm -1906 K. Dygert et al (2017) reported a viscosity of η = 0.22-1.45 Pa-s at experimental conditions, 1573-1873 K and 0.1-4.4 GPa, for a late Lunar Magma Ocean (LMO) analog. Although a direct comparison cannot be made because the composition of the late LMO (Fe-and Ti-rich ferrobasalt) is quite different from the present primitive lunar melts, both studies point to very low viscosities for these lunar melts.…”
Section: Comparison With Previous Work and Model Predictionssupporting
confidence: 89%
See 2 more Smart Citations
“…The corrected Uhlmann et al (1974) viscosity η = 0.54 Pa-s is higher than the one derived from our data η = 0.33 Pa-s; however the difference is not unacceptable considering experimental uncertainties. Recently, Sehlke and Whittington (2016) measured the 1 atm viscosity of a synthetic high-Ti lunar basalt (LM sample, 9.52 wt% TiO 2 ), and obtained η = 0.19 Pa-s at 1850 K, which extrapolates to η = 0.14 Pa-s at 1906 K. This value is again close to our present estimate for black glass composition η = 0.15 Pa-s at 1 atm -1906 K. Dygert et al (2017) reported a viscosity of η = 0.22-1.45 Pa-s at experimental conditions, 1573-1873 K and 0.1-4.4 GPa, for a late Lunar Magma Ocean (LMO) analog. Although a direct comparison cannot be made because the composition of the late LMO (Fe-and Ti-rich ferrobasalt) is quite different from the present primitive lunar melts, both studies point to very low viscosities for these lunar melts.…”
Section: Comparison With Previous Work and Model Predictionssupporting
confidence: 89%
“…For example, Liebske et al (2005) measured an activation energy E a = 197 kJ/mol for a peridotite liquid. For Ti-bearing ferrobasaltic melts, Chevrel et al (2014) reported E a = 179 kJ/mol for a 1.1 wt% TiO 2 and 20.36 wt% FeO composition, and Dygert et al (2017) derived E a = 153 kJ/mol for a 4.1 wt% TiO 2 and 29,9% FeO liquid. For lunar mare basalt compositions, the high-temperature data of Uhlmann et al (1974) on a synthetic Apollo15 green glass showed E a = 167 kJ/mol, and the more recent experimental measurements by Sehlke and Whittington (2016) on a high-Ti (9.54 wt% TiO 2 ) sample produced E a = 165 kJ/mol.…”
Section: Effects Of Temperature Pressure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HCP, pyroxene-dominated mixture spectra, spinel, or olivine were also detected in most of the surveyed central peaks where purest anorthosite was detected in previous studies (Donaldson Hanna et al, 2014;Yamamoto et al, 2010Yamamoto et al, , 2012. Head and Wilson (1992) proposed that as much as 50% of the lower crust is intruded by plutons; and Dygert et al (2017) proposed that the present-day lunar crust is composed of a relatively impure, old crust, later intruded by pure anorthositic diapirs. Alternatively, the anorthositic crust may be intruded later by more mafic plutons.…”
Section: Plagioclase Detectionsmentioning
confidence: 72%
“…Alternatively, the anorthositic crust may be intruded later by more mafic plutons. Head and Wilson (1992) proposed that as much as 50% of the lower crust is intruded by plutons; and Dygert et al (2017) proposed that the present-day lunar crust is composed of a relatively impure, old crust, later intruded by pure anorthositic diapirs. Both processes are consistent with the observation of PAN occurrences juxtaposed to mafic detections.…”
Section: Plagioclase Detectionsmentioning
confidence: 99%